Anti-inflammatory activity of Sanghuangporus sanghuang by suppressing the TLR4-mediated PI3K/AKT/mTOR/IKKβ signaling pathway. Issue 34 (13th April 2017) - Lin, Wang-Ching; Deng, Jeng-Shyan; Huang, Shyh-Shyun; Lin, Wan-Rong; Wu, Sheng-Hua; Lin, Hui-Yi; Huang, Guan-Jhong
Abstract : Sanghuangporus sanghuang (SS) is a mushroom that belongs to the genus Sanghuangporus and it is commonly called "Sangwhang" in Taiwan. Abstract : Sanghuangporus sanghuang (SS) is a mushroom that belongs to the genus Sanghuangporus and it is commonly called "Sangwhang" in Taiwan. It is popular in oriental countries and has been traditionally used as food and medicine. The mystery surrounding it was solved in 2012, when it was discovered. However, existing research has not extensively investigated the anti-inflammatory effect of sanghuang that grows on Morus trees. The aim of this study is to investigate the protective effects and underlying mechanism of SS on inflammation by lipopolysaccharide (LPS) induced in vitro and in vivo . Results showed that SS treatment markedly attenuated LPS-induced lung edema, by elevation of the levels of interleukin (IL)-1β, tumor necrosis factor (TNF)-α and IL-6 in bronchoalveolar lavage fluid (BALF) accompanied by a remarkable improvement of lung histopathological symptoms. Additionally, western blotting results suggest that anti-inflammatory effects of SS against the LPS-induced ALI may be due to its ability to inhibit the PI3K/Akt/mTOR/IKK, NF-κB and MAPK signaling pathways. Notably, our results suggest that SS suppresses LPS-induced ROS by inducing Nrf2 activation and HO-1, thioredoxin-1 expression in the lung tissues. Moreover, these findings suggest a potential application of SS in pulmonary inflammatory disease therapy.